THE LEVEL OF COMPLIANCE OF HEALTHCARE WORKERS IN PERFORMING HAND HYGIENE: A LITERATURE REVIEW - Selvia Rahayu; F Sri Susilaningsih; Maria Komariah (Journal of Nursing Care, 2021)
Compliance level of healthcare workers in performing hand hygiene is a significant aspect of patient safety goals. However, it is still not optimal and is one of the critical problems of many hospitals globally, including in Indonesia. The non-optimal consequence of hand hygiene compliance is hospital-associated infections since hands are an intermediary medium for transmitting infection. This literature aims to determine the level of compliance of health workers in performing hand hygiene and find out several matters that can be done so that the health worker's compliance can be optimal or increased. Review of articles through several electronic databases including PubMed and ProQuest, with the keywords "Compliance", "Hand Hygiene", "Health Workers", and "Hospital". Inclusion criteria include articles published between 2005 and 2019, health worker respondents, English language, full text and observation, or interview data collection techniques. The literature search found 212 articles, and after manual review, ten articles were identified and assessed using the JBI form (Joanna Briggs Institute). The literature review findings suggest that, following the intervention, the level of compliance of health workers in performing hand hygiene is still lacking and growing. The conclusion is that more significant support from the hospital (e.g., role models, audits, adequate infrastructure, education and repeated training), the greater the compliance of health workers in performing hand hygiene.